In vitro modulation of MMP-2 and MMP-9 in adult human sarcoma cell lines by cytokines, inducers and inhibitors - ROOMI, M.W. (D.A. Spandidos, 2013)
The highly aggressive adult sarcomas are characterized by high levels of matrix metalloproteinase (MMP)-2 and -9, which play crucial roles in tumor invasion and metastasis by degradation of the extracellular membrane leading to cancer cell spread to distal organs. We examined the effect of cytokines, mitogens, inducers and inhibitors on MMP-2 and MMP-9 secretion in chondrosarcoma (SW-1353), fibrosarcoma (HT-1080), liposarcoma (SW-872) and synovial sarcoma (SW-982) cell lines. The selected compounds included natural cytokines and growth factors, as well as chemical compounds applied in therapy of sarcoma and natural compounds that have demonstrated anticancer therapeutic potential. MMP-2 and MMP-9 secretions were analyzed by gelatinase zymography following 24-h exposure to the tested agents and quantitated by densitometry. Fibrosarcoma, chondrosarcoma, liposarcoma and synovial sarcoma showed bands corresponding to MMP-2 and MMP-9 with dose-dependent enhancement of MMP-9 with phorbol 12-myristate 13-acetate (PMA) treatment. In chondrosarcoma cells, tumor necrosis factor (TNF)-α had a stimulatory effect on MMP-9 and insignificant effect on MMP-2 and interleukin (IL)-1β stimulated MMP-9 and MMP-2. In fibrosarcoma and liposarcoma cells, TNF-α had a profound stimulatory effect on MMP-9, but no effect on MMP-2 and in synovial sarcoma an inhibitory effect on MMP-2 and no effect on MMP-9. IL-1β had a slight inhibitory effect on fibrosarcoma, liposarcoma and synovial sarcoma MMP-2 and MMP-9 except for MMP-9 in synovial sarcoma which showed slight stimulation. Lipopolysaccharide (LPS) stimulated expression of MMP-2 in fibrosarcoma and chondrosarcoma while inhibited it in liposarcoma. Doxycycline, epigallocatechin gallate and the nutrient mixture inhibited MMP-2 and MMP-9 in all cell lines. Actinomycin-D, cyclohexamide, retinoic acid, and dexamethasone inhibited MMP-2 and -9 in chondrosarcoma and fibrosarcoma cells. Our results show that cytokines, mitogens, inducers and inhibitors have an up or down regulatory effect on MMP-2 and MMP-9 expression in adult sarcoma cell lines, suggesting these agents may be effective strategies to treat these cancers.